Fortælling og kritik i teologien - Kemp, Peter (Religionsvidenskabeligt Tidsskrift, 1982)
In his official speech at the defence of Svend Bjerg’s theological dissertation “Den Kristne Grundfortælling” (The Fundamental Christian Story), Peter Kemp agrees to the idea of a narrative theology, but he argues that this theology should not – as Bjerg does – try to escape modern criticism of ideologies, illusions and perversities in story telling, because theological reply to criticism of religion or Christianity has no effect on the modern man if the critique is not taken seriously by the theologian and the stories are not evaluated from an ethical point of view. Kemp also considers that narrative theology is not necessarily opposed to existential philosophy, since philosophical analysis can demonstrate narrative quality of experience as a condition for the creation of stories and dramas. Finally, Kemp discusses Bjerg’s opposition to Paul Ricoeur’s and Kemp’s own concepts of symbol and metaphor. He argues that metaphor without symbol is a language without reference to transcendence.